Do acquiring-firm shareholders win or lose? Evidence from Europe. - Moreth, Robert (2005)
The effects of takeovers on the value of both, target and bidder firms have been studied by many researchers. While in the United States there is extensive empirical evidence on the effects of consolidation on share price movements, the empirical literature remains limited in Europe.